1997
DOI: 10.1021/ma970113b
|View full text |Cite
|
Sign up to set email alerts
|

Heat-Induced Gelation of Globular Proteins. 2. Effect of Environmental Factors on Single-Component and Mixed-Protein Gels

Abstract: In the first paper in this series, we investigated heat-induced gelation of single component systems of the globular protein, bovine serum albumin. A series of rheological experiments revealed that we can describe gelation time in terms of two physical parameters, concentration and temperature. In this paper we examine more complex systems, including the effect of pH and ionic strength, on heat-induced gelation of bovine serum albumin (BSA), and another globular protein, β-lactoglobulin (β-Lg). These factors s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 17 publications
(30 reference statements)
3
48
0
Order By: Relevance
“…The interaction between BSA and -lg in heat-induced gels has been studied previously (Tobitani & Ross-Murphy, 1997). It was found that the ratio of the two proteins to each other affected the gelation behaviour with the inclusion of BSA accelerating the formation of the heat-set gels.…”
Section: Introductionmentioning
confidence: 98%
“…The interaction between BSA and -lg in heat-induced gels has been studied previously (Tobitani & Ross-Murphy, 1997). It was found that the ratio of the two proteins to each other affected the gelation behaviour with the inclusion of BSA accelerating the formation of the heat-set gels.…”
Section: Introductionmentioning
confidence: 98%
“…It was found that the ratio of the two proteins to each other affected the gelation behavior with the inclusion of BSA accelerating the formation of heat-set gels (Tobitani and Ross-Murphy, 1997). Many studies in the past have elucidated this synergy with respect to various other physical parameters but have overlooked the effect of mixing these two differently sized proteins pertaining to the permeability and mobility of the matrix.…”
Section: Mixtures?mentioning
confidence: 99%
“…A smaller protein molecule can be easily incorporated into an interfacial film (Suttiprasit, et al, 1992;Hunter et al, 1991). The interaction between BSA and β-Lg in heat-induced gels has been studied previously (Tobitani & Ross-Murphy, 1997). It was found that the ratio of the two proteins to each other affected the gelation behavior, with the inclusion of BSA accelerating the formation of the heat-set gels.…”
Section: Introductionmentioning
confidence: 99%
“…A series of rheological experiments showed that gelation time can be described in terms of concentration or temperature (Tobitani and Ross-Murphy 1997a) and that the gelation kinetics were fairly accurately portrayed by their model system. In the same paper, they demonstrated that pH and ionic strength had a significant impact on the gelation time of binary mixed systems (BSA, ␤-lactoglobulin, and ␣-lactalbumin) although only reliable results were obtained for the BSA and ␤-Lactoglobulin systems, due to the complexity of the experiments (Tobitani and Ross-Murphy 1997b). It was, however, possible to relate the gelation behavior to the ratio of the 2 proteins present in the binary experimental design .…”
Section: Rheological Properties Of Protein Gelationmentioning
confidence: 99%